Hydrodynamic characterization of the first and second glide positions of the underwater stroke technique in breaststroke - Costa, L.; Ribeiro, J.; Figueiredo, P.; Fernandes, R. J.; Marinho, D.; Silva, A. J.; Rouboa, A.; Vilas-Boas, J. P.; Machado, L. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: The gliding constitutes a non-negligible part of the swimming races. The aim of this work was to experimentally study the first and second gliding positions of the breaststroke underwater stroke used after starts and turns at several gliding velocities by characterizing: gliding velocity (v); body cross sectional area (S); drag coefficient (CD); passive drag (D). METHODS: Six national level male swimmers participated in this study. A methodology similar to that described in Vilas-Boas et al. (in press) was used, namely determining S using planimetry while D and CD were assessed through inverse dynamics based upon the velocity to time curve of each glide, monitored through a swim-meter (Lima et al. 2006). RESULTS: The first glide presented higher mean values of v (1.50 ± 0.22m/s and 1.15 ± 0.24m/s) while the higher values of acceleration were verified in the second glide. D increased with v while CD decreased. Swimmers showed a smaller S in the first glide position than in the second (759.95 ± 124.12cm2 vs 814.46 ± 111.23cm2). DISCUSSION: The first glide obtained higher v values, as it follows wall impulse and has a better hydrodynamic position. For both glides, D increases with v, while CD decreases. The first one is characterised by lower D and CD values for all v, probably due to a parallel and concurrent effect of S and CD caused by the increased body length and slenderness associated with the flexed shoulders and extended arm position. Therefore, swimmers and coaches should stress the need for body position control during the glides, and the need of technical evaluation, control and advice to allow drag reductions during swimming performance, and not only emphasising propulsion increase capabilities.